Music as a Medium for Delivering Da'wah Material : Review of the Meaning of Da'wah in Maher Zain's Album Thank You Allah - Suhra, Sarifa; Herman, Renaldi (State Islamic Institute of Bone, Indonesia, 2022)
This paper examines music as a medium for delivering da'wah material. It aims to reveal in depth the meaning of da'wah in the album Thank You Allah by Maher Zain and show the da'wah material contained in it. To fail the data, primary data from Maher Zain's Thank You Allah Album video clip on YouTube Awakening Record is used, as well as audio music from the joox application. Data analysis was carried out using Charles Sander Pierce's theory of semiotic analysis, which focused on the signs arising in each data. To know and interpret the meaning in each sign in the data will be separated into 3 parts, namely: symbols, icons, and indices that will be continuous in the Triangle Meaning theory. The results showed that the existence of music on social media, provides an opportunity for musicians to preach to spread the teachings of Islam. through music. One of the most famous musicians in the religious music industry is Maher Zain. The first album released was Thank You Allah. The album contains 8 title tracks namely; baraka Allah lakuma, Ya Nabi Salam Alayka, Insha Allah, Palestine Will be Free, For the Rest of My life, Allah hi Allah Kiya Karo, Thank You Allah and Open Your Eyes, the songs contain material of da'wah aqidah, Shari'a/worship and also morals.